Pemanfaatan Nilai Tambah Komoditi Pepaya (Carica papaya L.) Pada Kelompok Pkk Sebagai Inisiasi Pembentukan Home Industry - Paskarada Juanti; Hetty Sri Mulyati; Rismawati Rismawati; Diah Mustika Lukitasari; Tiara Kumala; Benediktus Hendra P; Muhammad Syafi'ie; Nurdiansyah Nurdiansyah; Wilhemus Wilhemus; Hamidun Hamidun (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Melapi Village in South Putussibau District, Kapuas Hulu Regency, possesses abundant papaya (Carica papaya L.) resources; however, utilization remains largely limited to fresh consumption and use as a vegetable, failing to generate optimal economic value for the community. This community service program aims to enhance the knowledge, skills, attitudes, and interest of Melapi Village PKK (Family Welfare Empowerment) members regarding the processing of papaya into economically valuable products. The program's novelty lies in its application of an integrated mentoring model—combining extension services, demonstrations, hands-on practice, and continuous guidance—to strengthen community capacity in developing processed products based on local resources. The initiative involved 20 PKK members and proceeded through stages including needs assessment, extension sessions, demonstrations on making papaya jam and candied papaya, practical sessions, mentoring, and evaluation using pre-test and post-test instruments. Program effectiveness was analyzed using the Wilcoxon Signed-Rank Test. Results indicate a significant improvement in participants' knowledge, processing skills, attitudes, and interest following the mentoring (p<0.05). These findings demonstrate that the mentoring model effectively enhances community capacity to process papaya into value-added products, thereby opening opportunities for household business development, local product diversification, increased family income, and the sustainable economic strengthening of the PKK group.